Translational Model to Predict Pulmonary Pharmacokinetics and Efficacy in Man for Inhaled Bronchodilators. (27th December 2017) - Hendrickx, Ramon; Lamm Bergström, Eva; Janzén, David L. I.; Fridén, Markus; Eriksson, Ulf; Grime, Ken; Ferguson, Douglas
Abstract : Translational pharmacokinetic (PK) models are needed to describe and predict drug concentration‐time profiles in lung tissue at the site of action to enable animal‐to‐man translation and prediction of efficacy in humans for inhaled medicines. Current pulmonary PK models are generally descriptive rather than predictive, drug/compound specific, and fail to show successful cross‐species translation. The objective of this work was to develop a robust compartmental modeling approach that captures key features of lung and systemic PK after pulmonary administration of a set of 12 soluble drugs containing single basic, dibasic, or cationic functional groups. The model is shown to allow translation between animal species and predicts drug concentrations in human lungs that correlate with the forced expiratory volume for different classes of bronchodilators. Thus, the pulmonary modeling approach has potential to be a key component in the prediction of human PK, efficacy, and safety for future inhaled medicines.